P222 International research and guidelines on post-tuberculosis chronic lung disorders: a systematic scoping review. (December 2018) - van Kampen, SC; Wanner, A; Edwards, M; Harries, AD; Kirenga, B; Chakaya, J; Jones, R
Abstract : Introduction and objectives: Pulmonary tuberculosis (TB) is an important risk factor for chronic respiratory disease due to lung damage. Yet, the WHO End TB strategy does not mention post-TB chronic lung disorders (PTBLD) and programmatic interventions to address PTBLD are lacking. The aim of this study is to assess the scope of current guidelines and evidence on PTBLD to inform policy and research action. Methods: A systematic literature search was conducted following PRISMA guidelines. Eight databases (TRIP, International Guideline Library, MEDLINE/PubMed, EMBASE, Web of Science, Global Health, Cochrane Library) were searched for records on PTBLD published between 1 January 1990 and 1 December 2017. Non-English records, case series, conference abstracts and letters to editors were excluded. Data was extracted and charted on: publication year, location, PTBLD condition(s) and the main study outcome. Results: A total of 212 guidelines and 3661 articles were retrieved. After screening, only three international TB guidelines mentioned TB sequelae, but none described how to identify or manage the condition. A total of 156 articles addressed PTBLD: 54 (35%) mentioned unspecified TB sequelae; 47 (30%) specific post-TB conditions including aspergillosis, bronchial stenosis or bronchiectasis; 52 (33%) post-TB obstructive disease or lung function impairment; and 20 (13%) post-TB respiratory symptoms or chest x-ray abnormalities. The first two groups mostly assessed surgery and ventilation techniques for patient management, while the last two groups typically assessed prevalence and predictors of disease. Conclusions: This is the first review to provide a comprehensive overview of the current literature on PTBLD. The scope of evidence around the burden of PTBLD warrants inclusion and recognition of the problem in international guidelines. Research is now needed on early detection of PTBLD as well as patient management options that are suitable for high burden TB countries.